Energy state and properties controlling of metallic glasses by surface rejuvenation. (September 2019) - Liu, M.; Jiang, H.Y.; Liu, X.Z.; Gu, L.; Sun, Y.H.; Wang, W.H.; Bai, H.Y.
Abstract: Rejuvenation of metallic glasses (MGs), as to store more energy into the disordered system, can be achieved by many methods. Introducing hydrogen into MG is expected to be an efficient method to induce rejuvenation, yet it appears strange that arc-molten MGs with hydrogen have increased plasticity whereas electrically charged MG doesn't. In this work, we report that by leaving MGs in an alkaline environment, a predominant rejuvenation effect can be achieved, with both tensile ductility and compressive plasticity enhanced yet no deteriorate corrosion effects made. The enthalpy of the MG is increased from 0.95 to 1.77 kJ/mol and the energy conversion efficiency is increased as high as 86% at the optimal conditions. Although the method mainly rejuvenates the 10 μm-thick surface layers, the whole sample gets distinctly improved mechanical performance after the treatments, including enhanced high-temperature ductility and room-temperature plasticity. This method enlightens us that a control of the product and pace of the chemical reaction can rejuvenate MG, and provides a new fabrication approach for the MGs to achieve better mechanical performance. Highlights: Chemical immersion method is applied to achieve predominant rejuvenation of metallic glasses. The mechanical properties including tension/compression plasticity are greatly improved by the present chemical strategy. The energy-conversion efficiency is as high as 86%.